2020
DOI: 10.1016/j.ebiom.2020.103065
|View full text |Cite
|
Sign up to set email alerts
|

The age-related trajectory of visual attention neural function is altered in adults living with HIV: A cross-sectional MEG study

Abstract: Background Despite living a normal lifespan, at least 35% of persons with HIV (PWH) in resource-rich countries develop HIV-associated neurocognitive disorder (HAND). This high prevalence of cognitive decline may reflect accelerated ageing in PWH, but the evidence supporting an altered ageing phenotype in PWH has been mixed. Methods We examined the impact of ageing on the orienting of visual attention in PWH using dynamic functional mapping with magnetoencephalography (M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 125 publications
(157 reference statements)
1
21
1
Order By: Relevance
“…The test-retest reliability of oscillatory activity in pediatric populations may be very different, and it is widely known that such frequency-specific activity does change with development ( Fung et al, 2020 ; Heinrichs-Graham et al, 2020 ; Taylor et al, 2021 ; Uhlhaas et al, 2010 ; Whitford et al, 2007 ). Our sample also did not extend into older adult-hood, where either normative or pathologic aging may significantly alter the stability of these measurements ( Arif et al, 2020 ; Heinrichs-Graham et al, 2018 ; Spooner et al, 2019 ; Wiesman and Wilson, 2019 ). Additionally, long-term stability of activity may not generalize to clinical populations.…”
Section: Discussionmentioning
confidence: 97%
“…The test-retest reliability of oscillatory activity in pediatric populations may be very different, and it is widely known that such frequency-specific activity does change with development ( Fung et al, 2020 ; Heinrichs-Graham et al, 2020 ; Taylor et al, 2021 ; Uhlhaas et al, 2010 ; Whitford et al, 2007 ). Our sample also did not extend into older adult-hood, where either normative or pathologic aging may significantly alter the stability of these measurements ( Arif et al, 2020 ; Heinrichs-Graham et al, 2018 ; Spooner et al, 2019 ; Wiesman and Wilson, 2019 ). Additionally, long-term stability of activity may not generalize to clinical populations.…”
Section: Discussionmentioning
confidence: 97%
“…This testing was conducted across all participants and the entire frequency range (4 -100 Hz) and used an initial cluster threshold of p < 0.001 and 10,000 permutations. These methods are described in depth in our recent publications [11][12][13]65]. The resulting timefrequency clusters that survived permutation testing were selected for source imaging analyses.…”
Section: Sensor-level Statisticsmentioning
confidence: 99%
“…To our knowledge, no study to date has directly linked accelerated biological aging in PWH to the neurofunctional changes that occur in cognitively impaired PWH, which include deficits in visuospatial processing, attention, working memory, and motor function networks [10][11][12][13][14][15][16][17][18][19]. This paucity of work linking biological aging and functional brain activity persists despite a growing body of research showing chronological age-and disease-specific alterations to these functional networks in PWH.…”
Section: Introductionmentioning
confidence: 99%
“…Focusing on specific cognitive systems, such as the attentional systems, may facilitate our understanding of the mechanisms leading to dysfunction and provide more narrowly defined treatment targets. In this issue of EBioMedicine, Arif and colleagues [1] aimed to identify the neural factors contributing to attention deficits in 79 PWH (28 with HAND) compared to 94 HIV-uninfected individuals. The clinical significance of a focus on attention is high, as deficits in this cognitive domain are central to cognitive aging in PWH [2] and can affect the ability to perform daily tasks such as poor HIV medication adherence [3].…”
mentioning
confidence: 99%
“…However, the brain mechanisms underlying attention-deficits in PWH remain poorly defined. Arif et al [1] found that age differentially modulates the oscillatory dynamics underlying the attentional orienting processes in PWH and controls. They also reported an age-related increase in gamma oscillations in HAND vs. unimpaired PWH within three primary Ventral Attention Network nodes and attributed these findings to age-related compensation.…”
mentioning
confidence: 99%